Implementation Strengthening Education Character Student School Al-Anwar's Foundations Through School Culture - Anisah, Anis (CV. BImbingan Belajar Assyfa, 2023)
The nexus between education quality and the formation of quality human resources underscored by the values of Karakul Karima is pivotal in today’s world, where moral crises seem increasingly prevalent. The research conducted at SDN Al-Anwar in Pasuruan City’s Panggungrejo District for the academic year 2023/2024 delves into the intricate relationship between school culture and character education. By adopting a qualitative approach, this study illuminates how school culture can be both a boon and a bane to developing students' character, depending on its implementation. The findings of this research are multi-faceted, revealing that implementing character education through school culture requires a holistic approach. This includes the customary practice of core values, role modelling by teachers and staff, active stakeholder involvement, adherence to school regulations, strategic school branding, literacy efforts, and extracurricular activities. These components are vital in creating an environment that nurtures character development. However, challenges such as the varying capabilities of teachers in guiding and motivating students, the complexity in measuring the success of character value instillation, and the inconsistency of character education between school and home environments pose significant hurdles. Despite these obstacles, the study identifies critical supporting factors that can enhance the effectiveness of character education. These include the commitment of parents and teachers to instilling core values, the availability of tools to monitor achievements, and the consistent application of character education principles. The outcome of successfully implementing character education is profound, resulting in students who are not only academically competent but also embody high moral integrity and noble character. This research underscores the critical role of school culture in shaping the future generation. It highlights the need for concerted efforts to overcome challenges and maximize the benefits of character education.